Propuesta de Plan de Gestión Integral para desechos peligrosos hospitalarios generados en el manejo de la pandemia Covid-19 en el Hospital Básico Machachi del cantón Mejía provincia de Pichincha - Caiza Arias, Saul Alexander (2021)
This research was carried out at the Basic Hospital of Machachi in Pichincha province, whose purpose is elaborating a "Comprehensive Management Plan for hospital hazardous waste originated by the Covid-19 pandemic", which begins with the compilation of pertinent information on the proper management of waste and the current environmental regulations in the country to recognize hazardous hospital waste as well as the implementation of theoretical and technical tools; in this project, the non-experimental and scientific methodology was used -qualitative, supported by tools such as surveys and photographic evidence, on-site visit in order to verify the actual scenario of the basic hospital of Machachi in terms of the management of hospital hazardous waste; as a result of this visit, researchers evidenced the areas and activities that generate the most significant amount of hazardous waste and the shortcomings in each of these areas. Subsequently, the data obtained from the registered weighing of hospital hazardous waste for the year 2020 was verified, which showed an average result of 12062.4kg, which means 12.0624 tons, confirming that the areas that generate the most significant amount of hazardous hospital waste are: COVID-19 area, operating room, and emergency room respectively. Finally, the conclusions and recommendations for the study area were established, which are taken into account for the proposal of a comprehensive management plan for hazardous waste through compliance with environmental laws in force in the country. The Comprehensive Management Plan was carried out to improve the management of hazardous hospital waste and the environmental conditions within the basic hospital of Machachi through appropriate general protocols for their management and final disposal for the control of environmental risks and the pathological dangers in the health and population personnel of the Mejía canton.